(untitled) (Research, Society and Development, 2020)
Since the first detected cases of COVID-19 in Brazil, researchers have made a great effort to try to understand the disease. Understanding the impact of the disease on people can be instrumental in identifying which groups can be considered at risk. Therefore, this study researches a probabilistic model based on a statistical model of non-linear regression analyzing the following variables: age, if you are a health professional, if you are resident in the Metropolitan Region of Belém (RMB), State of Pará and gender with the objective of identifying those people who have a greater impact on the number of people infected and killed by COVID-19, that is, people who are more likely to die. To carry out the research, we used the data of all infected people by COVID-19 in the State of Pará until July 2020. It can be verified according to the proposal of the probabilistic model that elderly people, with a odds ratio of 1.69 (95% CI 1.52-1.88), residents of Metropolitan Region of Belém, with an odds ratio of 2.14 (95% CI 2.02 - 2.27) and men, with an odds ratio of 1.83 (95% CI 1.73 - 1.95) are groups of people with a higher risk of dying from diseases, while health professionals, with a 0.36 chance ratio (CI9 5% 0.29 - 0.45), are less likely to die.